2013
DOI: 10.3109/0886022x.2013.867812
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of nitric oxide and endothelin-1 in patients treated with continuous ambulatory peritoneal dialysis

Abstract: End-stage renal disease (ESRD) and its treatment modules affect almost all organs and organ systems including vascular endothelium. It is well known that disturbance of vasoactive substances (nitric oxide -NO and endothelin-1 -ET-1) production appears in these patients. There is a small number of studies which investigated serum levels of NO and ET-1 in ESRD patients treated with continuous ambulatory peritoneal dialysis (CAPD). Therefore our study aimed to measure serum levels of NO and ET-1 in this populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Uzun et al, also found that patients in PD, without HD, have lower levels of NO compared with HC (22). However, Kovačević et al, found increased levels of NO in CAPD (55). The reason of these different outcomes may be explained by the effect of PM solute transport rate among the patient in PD.…”
Section: Discussionmentioning
confidence: 98%
“…Uzun et al, also found that patients in PD, without HD, have lower levels of NO compared with HC (22). However, Kovačević et al, found increased levels of NO in CAPD (55). The reason of these different outcomes may be explained by the effect of PM solute transport rate among the patient in PD.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, the results of the studies that investigated the plasma levels and effects of NOx in patients with CKD were controversial. Some studies have supported that plasma NOx levels were lower in CKD patients (23,(26)(27). Total NO production was in a small number of patients with chronic renal failure, but the patient group was reported to be hypertensive during the investigation (28).…”
Section: Discussionmentioning
confidence: 98%
“…Physiological and pathophysiological mechanisms of CKD can cause damage of endothelium or blood vessels. It was shown that the disturbances of vasoactive substances like NOx production can result in significant hemodynamic problems and atherosclerosis in patients with CKD (23). The plasma concentration and urinary excretion of NO 2 and NO 3 (NOx; the stable oxidation products of NO) are now being widely used to give a measure of total NO production in vivo (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is unclear whether different type of dialysis (HD or CAPD) reduces or increases plasma concentrations of ET-1 and big ET-1, because previous studies, which only studied HD-induced changes in ET-1, have demonstrated conflicting results. 24,25 On the other hand, the role of ET-1 in lung diseases is significant and the number of respiratory tract disorders in which pathophysiology of this molecule holds a crucial role is rising. 19 Apart from pulmonary hypertension where ET-1 has a considerable effect, obstructive pulmonary diseases as well as pulmonary fibrosis should be also considered.…”
Section: Discussionmentioning
confidence: 99%